Platelet-Rich plasma: Basic science and biological effects - Kolber, M. J.; Purita, J.; Paulus, C.; Carreno, J. A.; Hanney, W. J. (Strength and Conditioning Journal, 2018)
Platelet-Rich Plasma (PRP) is an autologous biological intervention that seeks to augment the body's self-healing capacity. As a promising nonsurgical treatment option for musculoskeletal injuries, PRP has enthused significant interest among patients and sports medicine professionals. Owing to a growing range of clinical indications and excellent safety profile, sports medicine professionals are likely to encounter individuals who received or are considering prp. This article provides an overview of PRP, biological mechanisms, and evidence underpinning the utilization of PRP injections for musculoskeletal disorders. A companion article in this issue discusses considerations for sports medicine professionals managing individuals following PRP procedures.